Embedding Sulfur in MOF‐Derived Microporous Carbon Polyhedrons for Lithium–Sulfur Batteries. Issue 33 (25th June 2013) - Wu, Hao Bin; Wei, Shuya; Zhang, Lei; Xu, Rong; Hng, Huey Hoon; Lou, Xiong Wen (David)
<x xml:space="preserve">Abstract</x> Microporous carbon polyhedrons (MPCPs) are derived from unique MOF polyhedrons, and used as a model microporous carbon host for sulfur in Li–S batteries. Systematic investigations have been carried out to reveal the effects of several important parameters, such as the sulfur loading temperature, sulfur content, and the electrolyte. The MPCP/sulfur composite with sulfur exclusively embedded in micropores exhibit stable cycling performance with high Coulombic efficiency in both DOL/DME and EC/DEC electrolytes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>